Action Research on Improving Students' Speaking Proficiency in Using Cooperative Storytelling Strategy - Sharma, Dhani Ram (Journal of NELTA Surkhet, 2018)
Speaking is the first way to interact with others in the social community. Furthermore, the success in learning a language at first can be seen from the ability of the learner’s speaking. However, it is very hard for the second language learners to speak the foreign language, especially English. There are a lot of reasons why they get difficulties in speaking, such as lack of ideas to tell, lack of vocabularies to express the ideas, lack of the exposure to speak, and lack of the interesting teaching method or technique that can motivate them to speak. Thus, this research applied Cooperative Storytelling Strategy to Improve Students' Speaking proficiency of the students of grade 11in Nepal Rastriya Chandraganga Secondary School, Gagretal, Surkhet. This research was a collaborative classroom action research whose main purpose was to know whether or not storytelling strategy could improve the students’ speaking skill. Meanwhile, the specific purposes consisted of describing: (1) To implement storytelling strategy in 11th graders students at our School to improve their speaking skill. (2)To enhance their confidence in speaking skill and create fluency in speaking. The data of this research were got from the observations done by Story telling contest and Speaking test. The result showed that there was an improvement on students’ speaking proficiency after the implementation of storytelling strategy. The speaking test result in cycle two explained that the students’ speaking aspects got good progress. Storytelling improved their comprehension, fluency, vocabulary, grammar, and pronunciation. Thus, it can be said that storytelling strategy could improve students’ speaking skill.Journal of NELTA Surkhet,  Vol. 5 January, 2018, Page: 97-105